The manifestation of intertextuality in the poetry of Mukagali Makatayev - Zinollaeva А.К.; Baltymova М.Р. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article gives an interpretation of the intertext and analyzes the terms “intertext”, “intertextual”, “intertextuality”. The study of the problem of intertextuality is considered. The forms and properties of elements that have the ability to possess the function of intertext are analyzed, and the main structures and types are given. In the context of the concepts of intertext and intertextuality are the traditions, nature and national color of each country. Meanwhile, the author considers Kazakh poetry of the 70-90s of the twentieth century, including the achievement of Kazakh poetry in the field of knowledge of a person and his feelings, and a description of spiritual life. The verses of the famous Kazakh poet of our time Mukagali Makatayev are comprehensively analyzed. The poet’s works based on lyricism, romanticism and realism lead to cognitive comprehension. Elements having an intertext function are determined. Poems of M. Makatayev are composed of simple life phenomena and lead to a deep philosophy